Choice of Conflict Resolution Mechanisms among Pastoralists in Degahbour Woreda Somali Regional State, Ethiopia (Journal of International Relations and Peace, 2025)
Pastoralism has endured as a livelihood globally, but conflicts over natural resources have escalated due to various factors. This study assessed the choice of natural resource conflict resolution mechanisms among pastoralists in Degahbour Woreda, Somali Regional State, Ethiopia. A multistage sampling approach was used to select participants, and data was collected through household surveys, focus group discussions, and key informant interviews. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were presented descriptively. The binary logit model was employed to examine the factors influencing the choice of conflict resolution methods. The results revealed that a larger proportion of respondents (57.1%) preferred the local traditional resolution system over the governmental system (42.9%). Age, land size, livestock ownership, access to water, and household size positively influenced the choice of informal conflict resolution mechanisms, while educational level had a negative effect. Gender and occupation did not significantly influence the selection of resolution mechanisms. The findings suggest that customary institutions are deeply embedded in local contexts and perceived as more approachable and relevant for resolving resource-related disputes. Improving conflict resolution requires enhancing the effectiveness of traditional institutions and integrating them into formal systems, as well as promoting education and awareness of official mechanisms among younger and less educated groups.